Cross-cultural differences in food safety knowledge, attitudes and practices of food handlers working at restaurants in Kuwait - Allafi, Ahmad R; Al-Kandari, Dina; Al-abdeen, Jumanah; Al-Haifi, Ahmad R (Acta Biomedica Atenei Parmensis, 2020)
This study was conducted to assess the level of food safety knowledge, attitudes and practices among 273 Filipinos, Egyptians and Indians food handlers in Kuwait restaurants. The information was obtained through face to face interviews and questionnaires covering four sections: demographic characteristics, food safety knowledge, attitudes and practices. The results show that Filipinos, Egyptians and Indians food handlers had sufficient food safety knowledge particularly in the personal hygiene area. Filipinos were the best answering questions related to cross contamination and sanitation (p < 0.05). Egyptians and Indians lacked the knowledge about cross-contamination and sanitation, time and temperature control for food, and food pathogens. For attitudes, results show that Filipinos had excellent positive attitudes followed by Indians then Egyptians (p < 0.05). The three nationalities generally show very good practices mainly in personal hygiene. However, only 56 % of Egyptians and 57% of Indians avoided keeping cooked food in the temperature danger zone until served (p < 0.05). The study recommends that some aspects associated to cross-contamination, food pathogens and time and temperature control need to be stressed especially for Egyptians and Indians food handlers. Continuous food safety training for food handlers in Kuwait should become compulsory to reinforce food handlers in the areas which seem to be lacking.